Involvement of actin microfilament in regulation of pacemaking activity increased by hypotonic stress in cultured ICCs of murine intestine - Wang, Z Y; Huang, X; Liu, D H; Lu, H L; Kim, Y C; Xu, W X (Physiological research, 2015)
Distension is a regular mechanical stimulus in gastrointestinal (GI) tract. This study was designed to investigate the effect of hypotonic stress on pacemaking activity and determine whether actin microfilament is involved in its mechanism in cultured murine intestinal interstitial cells of Cajal (ICCs) by using whole-cell patch-clamp and calcium imaging techniques. Hypotonic stress induced sustained inward holding current from the baseline to -650+/-110 pA and significantly decreased amplitudes of pacemaker current. Hypotonic stress increased the intensity of basal fluorescence ratio (F/F0) from baseline to 1.09+/-0.03 and significantly increased Ca(2+) oscillation amplitude. Cytochalasin-B (20 microM), a disruptor of actin microfilaments, significantly suppressed the amplitudes of pacemaker currents and calcium oscillations, respectively. Cytochalasin-B also blocked hypotonic stress-induced sustained inward holding current and hypotonic stress-induced increase of calcium oscillations. Phalloidin (20 microM), a stabilizer of actin microfilaments, significantly enhanced the amplitudes of pacemaker currents and calcium oscillations, respectively. Despite the presence of phalloidin, hypotonic stress was still able to induce an inward holding current and increased the basal fluorescence intensity. These results suggest that hypotonic stress induces sustained inward holding current via actin microfilaments and the process is mediated by alteration of intracellular basal calcium concentration and calcium oscillation in cultured intestinal ICCs.
Keywords: vápníková signalizace; Animals; Female; mikrofilamenta; gastrointestinální motilita; ženské pohlaví; osmotický tlak; biologické hodiny; Mice; Osmotic Pressure; buněčný převod mechanických signálů; Mice, Inbred BALB C; kultivované buňky; myši; Cells, Cultured; Biological Clocks; Gastrointestinal Motility; Male; myši inbrední BALB C; Mechanotransduction, Cellular; Calcium Signaling; telocyty; zvířata; mužské pohlaví; Actin Cytoskeleton; Telocytes